1985
DOI: 10.1093/geronj/40.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Comparisons and Life Satisfaction of Elderly Adults

Abstract: The hypothesis that overall satisfaction with life is influenced by one's financial situation vis-a-vis significant others was tested. Respondents compared themselves financially to the relative, friend, and neighbor to whom they felt closest. Data from a 1980 community survey of persons 60 years of age and older showed that the better off financially respondents perceived themselves to be compared with the relative to whom they felt closest, the greater the life satisfaction. This effect was independent of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…Research has indicated that good health, functional ability, a sense of personal adequacy or usefulness, social participation, social networks, especially the existence of friends, social support and level of income have often been reported to be signi cantly associated with both psychological well-being and quality of life in older age (Maddox, 1963;Lowenthal & Haven, 1968;Markides & Martin, 1979;Kushman & Lane, 1980;Usui et al, 1985;Vailant, 1990;Bowling et al, 1996;Bowling & Windsor, 2001). Subjective self-ratings of well-being, and health have been reported to be more powerful than objective economic or socio-demographic indicators in explaining the variance in quality of life ratings (Markides & Martin, 1979;Kushman & Lane, 1980;Usui et al, 1985;Bowling et al, 1996;Bowling & Windsor, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that good health, functional ability, a sense of personal adequacy or usefulness, social participation, social networks, especially the existence of friends, social support and level of income have often been reported to be signi cantly associated with both psychological well-being and quality of life in older age (Maddox, 1963;Lowenthal & Haven, 1968;Markides & Martin, 1979;Kushman & Lane, 1980;Usui et al, 1985;Vailant, 1990;Bowling et al, 1996;Bowling & Windsor, 2001). Subjective self-ratings of well-being, and health have been reported to be more powerful than objective economic or socio-demographic indicators in explaining the variance in quality of life ratings (Markides & Martin, 1979;Kushman & Lane, 1980;Usui et al, 1985;Bowling et al, 1996;Bowling & Windsor, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Subjective self-ratings of well-being, and health have been reported to be more powerful than objective economic or socio-demographic indicators in explaining the variance in quality of life ratings (Markides & Martin, 1979;Kushman & Lane, 1980;Usui et al, 1985;Bowling et al, 1996;Bowling & Windsor, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the general finding of the large body of gerontological literature on the relationship between age and life satisfaction is that there is no age-related decline in life satisfaction (Larson, 1978;Herzog and Rodgers, 1981;Horley and Lavery, 1995;Diener and Suh, 1997;Smith et al, 1999 This section reviews some recent research on the relationship between health and life satisfaction: older studies include Markides and Martin (1979), Kushman and Lane (1980), Usui et al (1985), and Waters et al (1989).…”
mentioning
confidence: 99%
“…However, this study did not find a significant association between selfreported physical activity levels and life satisfaction among this sample of frail older adults. It is not impossible that the significant association between self-report physical conditions and life satisfaction observed in previous studies (Gupta and Korte 1994;Usui et al 1985) may not exist with a sample of exclusive frail older adults. However, given the limited generalizability of this study, further research is needed in order to fully understand the relationship between self-reported physical activity levels and life satisfaction among frail older adults.…”
Section: Discussionmentioning
confidence: 87%
“…Although previous research supported the importance of including health in life satisfaction studies, there has not been a consistent definition or measure of health. Generally speaking, in gerontological studies of subjective well-being, health has often been conceptualized as: (1) self evaluation of, or perceived, health status (e.g., Donnenwerth and Peterson 1992;Markides and Martin 1979;Russell 1990;Tran 1992), (2) satisfaction with one's own health (e.g., Krause 1991), or (3) self-report physical/activity conditions (e.g., Gupta and Korte 1994;Usui et al 1985). The current study uses all three definitions of health in exploring the relationship between quality of care of geriatric case management and quality of life (life satisfaction, in this case).…”
Section: Conceptual Frameworkmentioning
confidence: 99%